Productividad de forraje en un gradiente sucesional de bosque tropical seco en la costa de Jalisco - Lagunas Pérez, Mariana (Universidad Michoacana de San Nicolás de Hidalgo, 2022)
Successional vegetation is actually part of the extensive livestock production in dry tropics, nevertheless, knowledge regarding their capacity to produce forage, or the effect of continuous grazing on vegetation and forage productivity is still very limited. Regeneration by paddock abandonment could restore the region’s vegetation productivity, biodiversity and soil healthiness. Then again, the livestock’s extensive and constant grazing on the successional vegetation could deter the natural regeneration. The thesis objective was to identify the vegetation and forage (palatable vegetation for livestock) productivity on paddocks and successional sites with livestock grazing, as well as old mature forests without livestock, in order to analyze the livestock grazing effect on the successional progression. We hypothesized that due to the livestock’s selective consumption of forage, its production would diminish, while that of non-palatable vegetation would increase in proportion to the successional age of the grazing lands. Every month for a year, we collected the total amount of vegetation present within a squared section of 1x1m by 2m of height, in a fixed area isolated from livestock grazing (called systematic cut), and in a non-specific area subject to livestock grazing (called real foraging). The systematic cut measured the vegetation and forage productivity without the livestock’s selective grazing effect. The real foraging measured the livestock’s selective effect with free grazing on the same variables. Forage production decreased drastically as the successional development of the sites increased, including in old mature forests; the same occurred when comparing systematic cuts and real foraging. Forage production was high in active paddocks with real foraging which practice paddock rotation, but decreased considerably with systematic cuts. It seems important that moderating productive activities, and promoting rest in grazing lands and paddocks could allow regeneration, while sowing foraging species would increase forage production.

La vegetación sucesional es parte del sistema de producción ganadera extensiva en los trópicos secos, no obstante, existe información limitada sobre la capacidad de proveer forraje al ganado y el efecto del pastoreo continuo sobre la productividad de vegetación y forraje. Aunque el abandono de los potreros podría recuperar la productividad vegetal, la biodiversidad y la calidad del suelo de la región, el forrajeo extensivo y continuo del ganado en la vegetación sucesional, puede desviar esta regeneración. El objetivo en este trabajo fue conocer la productividad de vegetación y forraje (vegetación palatable al ganado) en potreros y sitios sucesionales con pastoreo ganadero, además de bosques conservados sin ganadería, para analizar el efecto del forrajeo en el proceso sucesional. Hipotetizamos que, debido al consumo selectivo del forraje por el ganado, la producción de forraje disminuiría y la de vegetación no palatable aumentaría con la edad sucesional de las parcelas. Durante un año, colectamos mensualmente la vegetación total presente en cuadros de 1x1m y 2m de altura en un área fija aislada del pastoreo (corte sistemático) y en un área no fija bajo pastoreo del ganado (pastoreo real). El corte sistemático y el pastoreo real evaluaron la productividad vegetal y de forraje fuera y dentro del efecto de la selección del ganado, respectivamente. La producción de forraje disminuyó drásticamente conforme aumentó la edad sucesional de los sitios, incluso en los bosques maduros; así mismo al comparar los cortes sistemáticos con el pastoreo real. La producción de forraje fue alta en los potreros activos con pastoreo real que se hace en rotación de parcelas, pero disminuyó considerablemente con el corte sistemático. Pareciera importante que moderar las actividades productivas y promover descansos en parcelas y potreros puede permitir la regeneración, a la vez que sembrar especies forrajeras incrementaría la producción de forraje.
Instituto de Investigaciones Agropecuarias y Forestales. Facultad de Biología. Facultad de Medicina Veterinaria y Zootecnia. Facultad de Agrobiología. Facultad de Químico Farmacobiología. Programa Institucional de Maestría en Ciencias Biológicas
Keywords: info:eu-repo/classification/cti/6; FB-M-2022-0203; Ecología y conservación; Regeneración; Sistema silvopastoril; Especies vegetales fijadoras-palatables; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/6671